1971
DOI: 10.1139/y71-037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Calcium, Phosphorus, and Vitamin D3 on Alkaline Phosphatase Activity of Intestinal Mucosa of Chicks

Abstract: Diets with varying levels of Ca, inorganic phosphorus (P1), and vitamin D3 were fed to chicks from 1 day of age. Alkaline phosphatase of intestinal mucosa was twofold higher at 3 weeks in female chicks fed 0.16% of P1 than in chicks fed 0.48% of P1 when the diets contained 7500 I.C.U. of vitamin D3 per kilogram and 1% of Ca. The effect of low dietary P1 was less pronounced when the diets contained 450 I.C.U. of vitamin D3 per kilogram and 1% of Ca but no definite pattern in enzyme activities due to level of P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The action of dietary Ca and Mg (1.5% Ca or 0.4% Mg versus control containing 0.6% Ca and 0.2% Mg) was subsequently verified [McCuaig et al, 1972;Kuan, 1965 (for Ca)]. Zinc deficiency lowered the phosphatase activity of several chick tissues while phosphorus deficiency elevated the intestinal (Davies et al, 1970;Motzok et al, 1971) and liver (McCuaig, 1970), enzyme. Phosphorus in excess had no effect (Mc-Cuaig et al, 1972).…”
mentioning
confidence: 95%
“…The action of dietary Ca and Mg (1.5% Ca or 0.4% Mg versus control containing 0.6% Ca and 0.2% Mg) was subsequently verified [McCuaig et al, 1972;Kuan, 1965 (for Ca)]. Zinc deficiency lowered the phosphatase activity of several chick tissues while phosphorus deficiency elevated the intestinal (Davies et al, 1970;Motzok et al, 1971) and liver (McCuaig, 1970), enzyme. Phosphorus in excess had no effect (Mc-Cuaig et al, 1972).…”
mentioning
confidence: 95%
“…Two further experiments in this laboratory have indicated that lincreascd dietary Ca can inorganic phosphorus (Pi) is inadequate (Motzok et al 1971 ;McCuaig and Motzok 1973). Since low phosphate diets (with normal Ca) also increase the enzyme activity in chicks McCuaig and Motzok 1972) it is probable that the dietary Ca/Pi ratio is the important factor regulating the enzyme.…”
mentioning
confidence: 99%